(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the article, the concept of culture is subjected to ontological analysis, as one the original models of the world and the result of human activity. The variety of manifestation of cultural elements in the semantic space-time dimension is considered on the example of Kyrgyz traditional artistic phenomena.